Comparative Analysis of Audio Steganography Methods - Beyin, Funda Aslantaş; Hanilci, Cemal (My University, 2022)
Information security has been one of the most important issues of all time for both individuals and companies. Delivering data to the correct recipient is crucial for personal data protection, the privacy of personal life, and national security. To this end, different methods have been developed over the years to hide information from malicious individuals. Steganography is one of the most important information hiding methods that received great attention. In this study, five different audio steganography techniques (least significant bit, echo hiding, wavelet coding, spread spectrum, and cepstrum) are utilized and a comparison of these techniques is performed on Turkish audio recordings.To this end, hidden messages of various sizes were embedded into 20 audio recordings from 10 male and 10 female speakers using different embedding algorithms. Signal-to-noise ratios (SNR) computed between stego and cover audio files show that embedded message length and frame size are the main factors that determine the quality. In addition, it is observed that there is no perceptual difference between the cover and stego audio recordings. Hence, the human auditory system is unable to determine whether an audio recording is authentic or conveys a hidden message. Experimental results show that as the message length increases, the average SNR value decreases irrespective of the steganography technique, as expected. The well-known least significant bit (LSB) technique yields the highest average SNR value among the five steganography methods. The spectrographic comparison of the cover and stego audio recordings shows that hiding the secret message in an original audio signal highly affects the high-frequency region more than the low-frequency components.
Keywords: Audio Steganography Techniques; Stego Audio; Human Auditory System; Secret Message; Data Hiding